Narsisisme Para Imam dalam Perayaan Ekaristi Suci - Sohmon Ranja Capah (Studia Philosophica et Theologica, 2019)
The Holy Eucharist is the Great Mystery of Salvation. In the celebration of the Eucharist, God through Jesus Christ in the Holy Spirit redeemed mankind. John Paul II calls the Eucharist a celebration of redemption because Jesus Christ, the High Priest, was present in a real and sacramental manner in the form of bread and wine which was changed into His Body and Blood. Jesus Christ is also present in the priests as in persona Christi. The Eucharist is a celebration of salvation because Jesus Christ sacrificed and became a spiritual meal for His people, the Church. In short, the Eucharist is the work of God Himself who calls His people to live and unite with Him. God is the main actor, owner and master of the celebration of the Holy Eucharist. Priests are alter Christiwho are chosen and ordained to serve the Eucharist. Priests act in the name of Christ not on themselves. They represent, work together and unite with Christ, the Author and the main Subject of the Eucharistic sacrifice, offering authentic sacrifices namely Christ Himself for the salvation of souls. So the priests were not justified in making the Holy Eucharist a narcissistic stage. They may not carry out self-assertive actions and try to attract the attention of the faithful to themselves.